Enhanced electron field emission properties of high aspect ratio silicon nanowire-zinc oxide core-shell arrays - Prabhakar, Rajiv Ramanujam (2013)
The enhanced electron field emission (EFE) properties of high aspect ratio, vertically aligned SiNW–ZnO core–shell arrays are presented. These core–shell arrays are prepared by a thin, controlled, highly crystalline and conformal coating of zinc oxide as shell using the plasma assisted-atomic layer deposition (PA-ALD) route on vertically aligned silicon nanowire arrays core. The core–shell nanostuctures are confirmed by HRTEM imaging along with the individual elemental mapping demonstrating the conformal deposition of 10 nm ZnO on the SiNWs. EFE properties of va-SiNW–ZnO core–shell arrays showed a high emission current density of 51 μA cm−2 and a low turn on field of 7.6 V μm−1 (defined at a current density of 1 μA cm−2) compared to the 3.2 μA cm−2 emission current density and 9.1 V μm−1 turn on field for SiNWs. The field enhancement factor (β) of 4227 for the devices demonstrates that these core–shell nanowire arrays are excellent field-emitters. Such an enhancement in the field emission originates from the details of the band structure of this peculiar material combination resulting in good electron transport from SiNW to ZnO as evident from the band diagram of the core–shell material. This is further supported by the conducting AFM studies where lowering in threshold voltage by 1 eV confirms the role of ZnO coating in the enhancement of the emission characteristics.